HISTOLOGY OF THE PAROTID SALIVARY GLAND OF THE AFRICAN PALM SQUIRREL (Epixerus ebii) - Ikpegbu Ekele (Revista de la Facultad de Ciencias Veterinarias, UCV, 2013)
he parotid salivar y gland microscopic morphology of the adult African Palm squirrel ( Epixerus ebii) was investigated. This study was carried out to provide the basic histology of this organ in the palm squirrel, as there is dearth of information of its microscopic morphology from available literature. This becomes more important as the increasing use of this species of rodent as a pet and animal of importance in African game reserves for tourist attraction. The possibility of its domestication as a ready source of animal protein is also growing. Hence the need to understand the digestive biology to help animal nutritionist in feed formulation. The histology revealed the presence of only serous secretory acini cells. The serous cells were triangular to polyhedral shaped with a roundish basally located nucleus inside the mostly pinkish granulated cytoplasm. Myoepithelial cells were seen around the secretory cells and the intercalated ducts. The intralobular ducts of intercalated and striated ducts were lined by simple cuboidal and simple columnar cells, respectively. The excretor y duct seen in the surrounding connective tissue was lined by stratified cuboidal cells. The granules in the cytoplasm of serous cells must be the digestive enzyme amylase that initiates carbohydrate digestion. This well developed serous parotid salivary gland reflects the need for efficient carbohydrate digestion since the animal forages on fruits and nuts that are rich in carbohydrates. The granules could also contain lysozymes which serve in local defense against pathogenic agents in the oral cavity. This study for the first time documents the normal histology of the parotid salivary gland in this species, hence filling the knowledge gap that will help biologists to investigative more profundly. It will also help wild life veterinarians in diagnosis disease.